2018
DOI: 10.1016/j.jbiomech.2018.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Vastus lateralis and vastus medialis produce distinct mediolateral forces on the patella but similar forces on the tibia in the rat

Abstract: Improper activation of the quadriceps muscles vastus medialis (VM) and vastus lateralis (VL) has been implicated in the development of patellofemoral pain (PFP). This explanation of PFP assumes that VM and VL produce opposing mediolateral forces on the patella. Although studies have provided evidence for opposing actions of VM and VL on the patella, other studies have suggested that their actions might be similar. In this study, we took advantage of the experimental accessibility of the rat to directly measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 44 publications
3
13
0
Order By: Relevance
“…Although previous studies have demonstrated a strong correlation between the activity of VM and VL [10,[29][30][31], the functional role of this correlation has not been clear. Since VM and VL have the same contribution to task variables and produce opposing mediolateral patellar forces [11], their strong correlation is consistent with both simplification of task performance [16,19] and regulation of internal joint stresses [29,32,33]. Similarly, the observation that RF could be controlled more independently than the vasti [31,34] is also consistent with both interpretations, as RF has a different task action from VM and VL [35,36] and produces minimal mediolateral patellar force (Fig.…”
Section: Functional Role Of Muscle Co-variation In Quadricepssupporting
confidence: 73%
See 3 more Smart Citations
“…Although previous studies have demonstrated a strong correlation between the activity of VM and VL [10,[29][30][31], the functional role of this correlation has not been clear. Since VM and VL have the same contribution to task variables and produce opposing mediolateral patellar forces [11], their strong correlation is consistent with both simplification of task performance [16,19] and regulation of internal joint stresses [29,32,33]. Similarly, the observation that RF could be controlled more independently than the vasti [31,34] is also consistent with both interpretations, as RF has a different task action from VM and VL [35,36] and produces minimal mediolateral patellar force (Fig.…”
Section: Functional Role Of Muscle Co-variation In Quadricepssupporting
confidence: 73%
“…Our ability to disambiguate between interpretations of muscle co-variation relied on the conceptual simplicity of the knee biomechanics in the rat. The rat knee joint provides a clear separation between the action of quadriceps muscles on task performance and internal joint stresses, allowing us to distinguish between the different interpretations of muscle co-variation [11,22]. In other joints and animals such a separation may not be as clear, and the actions of muscles on these different aspects of motor control may need to be estimated using detailed biomechanical models [52,53].…”
Section: Interpretation Of Muscle Co-variation Patterns In Other Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the experiments reported here, we overcome these challenges by taking advantage of the unique properties of the rat knee joint ( Figure 1a ). Activation of the quadriceps muscles vastus lateralis (VL) and vastus medialis (VM) in the rat produces very similar forces at the distal tibia and so will produce similar joint torques ( Sandercock et al, 2018 ). These muscles therefore have redundant contributions to task performance.…”
Section: Introductionmentioning
confidence: 99%